1992
DOI: 10.1152/jappl.1992.72.2.760
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines and regional hemodynamics during isovolemic hemodilution in anesthetized pigs

Abstract: The effects of stepwise isovolemic hemodilution on systemic and regional hemodynamics, oxygen flux, and circulating catecholamines were studied in six pigs anesthetized with midazolam and fentanyl. Reduction of the hematocrit from 28 to 9% resulted in doubling of the cardiac output, mainly due to an increase in stroke volume. Regional blood flows, measured using the radioactive microsphere technique, showed an increase in blood flow to all organs except liver (hepatic artery fraction) and adrenals, with a redi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 0 publications
2
25
1
Order By: Relevance
“…They concluded that ''an intact autonomic nervous system is necessary for the total circulatory response to anemia''. 70 Although one study was unable to demonstrate an increase in systemic catecholamines after acute hemodilution, 71 another more recent study demonstrated a sudden acute fourfold increase in systemic noradrenalin levels, suggestive of increased sympathetic activity. 14 The sudden increase in systemic noradrenalin occurred much earlier than increases in adrenaline and dopamine, suggesting that spillover from adrenergic nerve activity may have played a role.…”
Section: Hemodilution Results In Activation Of the Sympathetic Nervoumentioning
confidence: 99%
“…They concluded that ''an intact autonomic nervous system is necessary for the total circulatory response to anemia''. 70 Although one study was unable to demonstrate an increase in systemic catecholamines after acute hemodilution, 71 another more recent study demonstrated a sudden acute fourfold increase in systemic noradrenalin levels, suggestive of increased sympathetic activity. 14 The sudden increase in systemic noradrenalin occurred much earlier than increases in adrenaline and dopamine, suggesting that spillover from adrenergic nerve activity may have played a role.…”
Section: Hemodilution Results In Activation Of the Sympathetic Nervoumentioning
confidence: 99%
“…Furthermore, we closely monitored heart rate and blood pressure, which quickly respond to pain, and found no sudden increases throughout the experiment. The doses of anesthetics are in the range commonly used for anesthesia in pigs with (20,29,45) and without (16) muscle relaxants. This procedure is in accordance with the American Physiological Society "Guiding Principles in the Care and Use of Animals," which states that muscle relaxants may be used in conjunction with drugs known to produce adequate anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Large differences in the tolerance of organ systems to conditions of decreased O 2 delivery (DO 2 ) exist. However, as soon as the systemic oxygen delivery falls below a critical point, compensatory mechanisms are getting insufficient and oxygen consumption (V O 2 ) becomes dependent on supply (4,28,32,36,38). Although compensatory mechanisms preserve vital organ oxygenation over a wide range of decreasing hematocrit, they may impair tissue oxygenation of critical organs (34,37).…”
mentioning
confidence: 99%